The Influence Of Probing Question Technique Usage In Teaching-Learning Activities On Students’ Critical Thinking Ability - Mohzana Mohzana; Tofhan Mamonto; Enny Diah Astuti; Indah Asmarany; Ilham Arief (Mudir : Jurnal Manajemen Pendidikan, 2023)
The aim of this study was to compare how conventional learning and probing question strategies affected students' development of their mathematical critical thinking skills. A junior high school served as the site for this study. A quasi-experimental study design with a post-test only control design was adopted as the research methodology. Cluster random sampling techniques were used in this investigation. An assessment of mathematical critical thinking abilities was conducted using a descriptive instrument in this study. A two-way ANOVA is the method of data analysis employed. The outcomes revealed that learners who learned using the probing question technique and those who learned conventionally had different levels of mathematics critical thinking abilities; the categories of high, medium, and poor prior mathematical knowledge show variances in the pupils' mathematical critical thinking abilities; students' mathematical critical thinking abilities are not affected by the probing question technique or their existing mathematical knowledge.